The deubiquitinase Usp7 in Drosophila melanogaster is required for synaptonemal complex maintenance. - Lake, C.M.; Gardner, J.; Briggs, S.; Yu, Z.; McKown, G.; Hawley, R.S. (Proceedings of the National Academy of Sciences of the United States of America, 2024)
Meiosis is a form of cell division that is essential to sexually reproducing organisms and is therefore highly regulated. Each event of meiosis must occur at the correct developmental stage to ensure that chromosomes are segregated properly during both meiotic divisions. One unique meiosis-specific structure that is tightly regulated in terms of timing of assembly and disassembly is the synaptonemal complex (SC). While the mechanism(s) for assembly and disassembly of the SC are poorly understood in Drosophila melanogaster, posttranslational modifications, including ubiquitination and phosphorylation, are known to play a role. Here, we identify a role for the deubiquitinase Usp7 in the maintenance of the SC in early prophase and show that its function in SC maintenance is independent of the meiotic recombination process. Using two usp7 shRNA constructs that result in different knockdown levels, we have shown that the presence of SC through early/mid-pachytene is critical for normal levels and placement of crossovers.